Using Animal Retribution Fiction for the Promotion of Environmental Awareness: the Case for a Reinterpretation of Daphne Du Maurier's "The Birds" - Xavier LACHAZETTE (E-REA)
In the search for effective means of representing and conveying the urgency of the environmental crisis facing humanity in the coming decade, not all images hit the mark with the same forcefulness. Al Gore's phrase "An Inconvenient Truth", for instance, strikes one's imagination far less than the "house on fire" metaphor popularized by French President Jacques Chirac and Swedish activist Greta Thunberg. Another powerful image is to be found in Daphne Du Maurier's allegorical novella "The Birds" (1952), which focuses on a small Cornish community's fight for survival when organised hosts of winged creatures take to killing humans in the wake of a sudden climate change. Not only is that story visionary in its suggestion that self-sufficiency and degrowth are more viable or sustainable than current economic systems, but it offers us today a striking metaphor for the catastrophic backlash that humanity needs to avoid. Du Maurier thus creates a frightful tale of animal retribution in which preys are suddenly turned into predators, and human beings need to face the implacable anger they have aroused if they wish to prevent a sort of Silent Spring (Rachel Carson) in reverse.